2015
DOI: 10.1016/j.ijsu.2015.06.078
|View full text |Cite
|
Sign up to set email alerts
|

The association of calcaneal spur length and clinical and functional parameters in plantar fasciitis

Abstract: The size of the calcaneal spur is an important parameter correlated with pain and functional scores in PF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
8

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 13 publications
2
31
0
8
Order By: Relevance
“…Another study conducted by Kuyucu et al documented the correlation of plantar spur length with clinical and functional status in patients with plantar fasciitis. They concluded that patients with larger spur had significantly worse pain and function than those with smaller spur 11 . In 2015, an endoscopic study conducted by Zhou et al classified PS into two types based on the location of PS in relation with plantar fascia i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Kuyucu et al documented the correlation of plantar spur length with clinical and functional status in patients with plantar fasciitis. They concluded that patients with larger spur had significantly worse pain and function than those with smaller spur 11 . In 2015, an endoscopic study conducted by Zhou et al classified PS into two types based on the location of PS in relation with plantar fascia i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology of calcaneal spur remains not fully understood, but the traditional explanation on the formation of bony heel spur is the longitudinal traction hypothesis: inflammation and reactive ossification of the enthesis, particularly chondroidal and intramembranous ossification, are due to excessive traction of the origin of the plantar fascia at the calcaneal tuberosity [[3], [4], [5], [6], [7]]. …”
Section: Introductionmentioning
confidence: 99%
“…Obesity, pes planus, microtrauma, aging, and specific sport activities such as running, jumping, and ballet are all recognized risk factors that contribute to heel spur formation [1[3], [4], [5], [6]]. There is consensus that a calcaneal spur is a common cause of heel pain [14,4,5,6]; however, some cases are asymptomatic, with most studies reporting ∼16% and Bartold [8] reporting as much as ∼30%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations